2011
DOI: 10.1111/j.1574-6968.2011.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone protects against Staphylococcus aureus pneumonia

Abstract: Staphylococcus aureus is a versatile pathogen that can cause life-threatening infections. The growing emergence of methicillin-resistant S. aureus strains and a decrease in the discovery of new antibiotics warrant the search for new therapeutic targets to combat infections. Staphylococcus aureus produces many extracellular virulence factors that contribute to its pathogenicity. Therefore, targeting bacterial virulence as an alternative strategy to the development of new antimicrobials has gained great interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…The DU 1090 strain, an Hla-mutant of S. aureus 8325-4, caused almost no cell injury to the S. aureus in an A549 cell co-culture system. However, A549 cells were killed when cultured with S. aureus 8325-4 (Qiu et al 2011a). These studies suggested that Hla can be considered as a potential anti-virulence therapeutic target for against S. aureus infection, particularly for S. aureus pneumonia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The DU 1090 strain, an Hla-mutant of S. aureus 8325-4, caused almost no cell injury to the S. aureus in an A549 cell co-culture system. However, A549 cells were killed when cultured with S. aureus 8325-4 (Qiu et al 2011a). These studies suggested that Hla can be considered as a potential anti-virulence therapeutic target for against S. aureus infection, particularly for S. aureus pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have indicated that many natural products can affect the production of Hla by S. aureus and have therapeutic effects on S. aureus pneumonia in a mouse model (Qiu et al 2010(Qiu et al , 2011aWang et al 2015;Zhou et al 2015). Imperatorin (9-(3-Methylbut-2-enoxy)-7-furo[3, 2-g]chromen-7-one), a furocoumarin compound (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria have become an important component of the apoptosis execution machinery, cytochrome c, initiator in the mitochondrial apoptosis pathway, and can be released from the intermembrane of mitochondria after mitochondria depolarization (106)(107)(108).…”
Section: Targeting Cancer Cells By Mitochondriamediated Apoptosis Patmentioning
confidence: 99%
“…Current literature shows that alantolactone and isoalantolactone possess various antimicrobial [3], antiinflammatory [4], and antitumor activities [5][6][7][8][9][10] both in vivo and in vitro. A recent study done by the team revealed that alantolactone and isoalantolactone could significantly relieve irritable bowel syndrome (IBS) by regulating neurotransmitters, gastrointestinal hormones, and intestine propulsive movement.…”
Section: Introductionmentioning
confidence: 99%